2020
DOI: 10.1371/journal.pone.0228254
|View full text |Cite|
|
Sign up to set email alerts
|

Life history of northern Gulf of Mexico Warsaw grouper Hyporthodus nigritus inferred from otolith radiocarbon analysis

Abstract: Warsaw grouper, Hyporthodus nigritus, is a western Atlantic Ocean species typically found at depths between 55 and 525 m. It is listed as a species of concern by the U.S. National Marine Fisheries Service and as near threatened by the International Union for the Conservation of Nature. However, little information exists on the species' life history in the northern Gulf of Mexico (nGOM) and its stock status in that region is currently unknown. Age of nGOM Warsaw grouper was investigated via opaque zone counts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…reported that most age and growth studies did not provide estimates of the precision of ageing and that APE and C.V.were statistically sound measures of the precision of ageing. The APE (5.3) and C.V.(6.6) shown in this study were slightly higher than those of the Brazilian goatfish Pseudupeneus maculatus(Santana et al, 2006;(Barnett et al, 2020;Burton et al, 2016;Gordo et al, 2016;Potts et al, 2016). Thus, the precision of age determination in this study is considered acceptable.The authors found that the periodicity of opaque bands in otoliths of M. vanicolensis is annual, with a peak in July-September T A B L E 1…”
supporting
confidence: 44%
See 1 more Smart Citation
“…reported that most age and growth studies did not provide estimates of the precision of ageing and that APE and C.V.were statistically sound measures of the precision of ageing. The APE (5.3) and C.V.(6.6) shown in this study were slightly higher than those of the Brazilian goatfish Pseudupeneus maculatus(Santana et al, 2006;(Barnett et al, 2020;Burton et al, 2016;Gordo et al, 2016;Potts et al, 2016). Thus, the precision of age determination in this study is considered acceptable.The authors found that the periodicity of opaque bands in otoliths of M. vanicolensis is annual, with a peak in July-September T A B L E 1…”
supporting
confidence: 44%
“…The APE (5.3) and c.v. (6.6) shown in this study were slightly higher than those of the Brazilian goatfish Pseudupeneus maculatus (Santana et al ., 2006; APE: 2.3, c.v. : 4.7) and the Okinawan Mulloidichthys flavolineatus (Samejima et al ., 2021; APE: 3.3, c.v. : 4.4) but still within the acceptable levels of APE and c.v. , proposed by Campana (2001), of 5.5 and 7.6%, respectively. Furthermore, they were comparable to other well‐studied commercial fishes such as Lutjanidae, Scaridae and Serranidae (Barnett et al ., 2020; Burton et al ., 2016; Gordo et al ., 2016; Potts et al ., 2016). Thus, the precision of age determination in this study is considered acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…One extreme example of this was recently documented in the western Atlantic for warsaw grouper Hyporthodus nigritus [77,78]. Growth increment counts from thin sections of sagittal otoliths of warsaw grouper were validated [77] and the ageing method produced a new maximum age estimate of 91 y for an individual fish [78] that exceeded the previous maximum reported age of 61 by 30 y [76].…”
Section: Longevity Growth and Population Age Structurementioning
confidence: 96%
“…Previous spine-based ageing work on queen triggerfish reported a maximum of 7 y [53] for the north Caribbean and 14 y [19] for the species. Several age estimation validation studies utilizing Δ 14 C published in the past 15 y have noted major increases in longevity estimates for a multitude of fishes [36,[74][75][76][77]. One extreme example of this was recently documented in the western Atlantic for warsaw grouper Hyporthodus nigritus [77,78].…”
Section: Longevity Growth and Population Age Structurementioning
confidence: 99%
“…Otoliths, mainly composed of calcium carbonate and organic matrix, play vital roles in sound sensing, balance, linear acceleration, and gravity in bony fishes ( Schulz-Mirbach et al, 2019 ). Moreover, otoliths are widely applied in fisheries sciences, such as evaluation of fish populations or population migration patterns, and are essential for paleoichthyological and archeological studies ( Barrett, 2019 ; Barnett et al, 2020 ; Heimbrand et al, 2020 ). Several critical genes, including Otoconin-90 (Oc90), secreted protein acidic and rich in cysteine (SPARC), SPARC-like1 (SPARCL1), otopetrin-1 (otop1), otolin-1 (otol1), and Otolithmatrixprotein-1 (OMP-1), have been identified to be related to otolith growth and formation in various vertebrates including bony fishes ( Hurle et al, 2003 ; Murayama et al, 2005 ; Kang et al, 2008 ; Petko et al, 2008 ; Xu et al, 2016b ; Hołubowicz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%